Ring finger protein 128 promotes, rather than inhibits, colorectal cancer progression by regulating the Hippo signaling pathway - Ning, Shili; Chen, Yuzhuo; Wang, Guangzhi; Liu, Yongtai; Yang, Yingchi; Zhang, Zhongtao (Frontiers in Oncology, 2022)
Background Colorectal cancer is a common malignancy of the gastrointestinal tract, and its incidence and mortality rates have increased in recent years. RNF128 is an E3 ubiquitin ligase that plays an important role as a suppressor gene or oncogene in various cancers, but its mechanism in colorectal cancer is not yet clear. The aim of this study was to investigate the role and mechanism of RNF128 in colorectal cancer. Methods The expression of RNF128 in colorectal cancer tissues was assessed by immunohistochemistry and western blotting. The proliferation ability of colorectal cancer cells was measured by colony formation assay and CCK-8 assay, the migration and invasion ability of colorectal cancer cells was measured by wound healing assay and transwell assay, and the protein expression levels of the Hippo signaling pathway and its target gene were examined by western blotting. Immunoprecipitation was used to assess the interaction of RNF128 with MST. In vivo, a xenograft tumor model was used to detect the effect of RNF128 on tumor growth. Results At the tissue level, the expression level of RNF128 was significantly higher in colorectal cancer tissues than in adjacent normal tissues. In LoVo cells and HCT116 cells, the proliferation, migration and invasion abilities were significantly reduced with RNF128 knockdown. At the protein level, knockdown of RNF128 resulted in significant activation of the Hippo signaling pathway. In vivo experiments, the volume and weight of xenograft tumors in nude mice were significantly decreased compared with those in the normal control group with RNF128 knockdown. Conclusion RNF128 promotes the malignant behaviors of colorectal cancer cells by inhibiting the Hippo signaling pathway, which may provide a new target for colorectal cancer prevention and treatment.